Anchored Multiplex PCR Custom Melanoma Next Generation Sequencing Panel for Analysis of Circulating Tumor DNA - Diefenbach, Russell J.; Lee, Jenny H.; Stewart, Ashleigh; Menzies, Alexander M.; Carlino, Matteo S.; Saw, Robyn P. M.; Stretch, Jonathan R.; Long, Georgina V.; Scolyer, Richard A.; Rizos, Helen (Frontiers in Oncology, 2022)
Detection of melanoma mutations using circulating tumor DNA (ctDNA) is a potential alternative to using genomic DNA from invasive tissue biopsies. To date, mutations in the GC-rich TERT promoter region, which is commonly mutated in melanoma, have been technically difficult to detect in ctDNA using next-generation sequencing (NGS) panels. In this study, we developed a custom melanoma NGS panel for detection of ctDNA, which encompasses the top 15 gene mutations in melanoma including the TERT promoter. We analysed 21 stage III and IV melanoma patient samples who were treatment-naïve or on therapy. The overall detection rate of the custom panel, based on BRAF/NRAS/TERT promoter mutations, was 14/21 (67%) patient samples which included a TERT C250T mutation in one BRAF and NRAS mutation negative sample. A BRAF or NRAS mutation was detected in the ctDNA of 13/21 (62%) patients while TERT promoter mutations were detected in 10/21 (48%) patients. Co-occurrence of TERT promoter mutations with BRAF or NRAS mutations was found in 9/10 (90%) patients. The custom ctDNA panel showed a concordance of 16/21 (76%) with tissue based-detection and included 12 BRAF/NRAS mutation positive and 4 BRAF/NRAS mutation negative patients. The ctDNA mutation detection rate for stage IV was 12/16 (75%) and for stage III was 1/5 (20%). Based on BRAF, NRAS and TERT promoter mutations, the custom melanoma panel displayed a limit of detection of ~0.2% mutant allele frequency and showed significant correlation with droplet digital PCR. For one patient, a novel MAP2K1 H119Y mutation was detected in an NRAS/BRAF/TERT promoter mutation negative background. To increase the detection rate to >90% for stage IV melanoma patients, we plan to expand our custom panel to 50 genes. This study represents one of the first to successfully detect TERT promoter mutations in ctDNA from cutaneous melanoma patients using a targeted NGS panel.